Multinational Corporations - بعيرة د. ابو بكر مصطفى (Dirasat in Economics and Business, 1982)
During the past few decades the volume of international trade has increased considerably. It went up from an estimated 57 billion in 1950 to about 1507 billion in 1979. Both as a cause and a corollary of this emerged phenomenon of the Multinational corporations (MNC's). In 1980 Fortune magazine's 500 largest corporations reached 1650 billion in profits, and about 16 million people working for them (see table 1,2 and 3 of the main article in Arabic).